2020
DOI: 10.1186/s12992-020-00635-7
|View full text |Cite
|
Sign up to set email alerts
|

Data and cooperation required for Venezuela’s refugee crisis during COVID-19

Abstract: The deteriorating political and economic situation in Venezuela has ramifications far beyond the Latin American country’s borders as almost five million Venezuelans fled and migrated into countries in the region due to the crisis at home. The scarcity of health services, the lack of information sharing, and the absence of reliable data in Venezuela create challenges for confronting developing health emergencies and disease outbreaks. The need for accurate data is especially dire given the current COVID-19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Furthermore, we observed that the majority of the surveyed personnel were not comfortable to perform their tasks during the current pandemic (59.8%). Venezuela suffers from a complex humanitarian crisis, their health system presents insufficient infrastructure, personnel and supplies, mentioned as “collapsed” previous to COVID-19 ( 35 ); in light of this recent pandemic, HCWs may present higher fear and restraint to work under these conditions, which imply a greater risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that the majority of the surveyed personnel were not comfortable to perform their tasks during the current pandemic (59.8%). Venezuela suffers from a complex humanitarian crisis, their health system presents insufficient infrastructure, personnel and supplies, mentioned as “collapsed” previous to COVID-19 ( 35 ); in light of this recent pandemic, HCWs may present higher fear and restraint to work under these conditions, which imply a greater risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil poor living conditions, difficulty accessing the health service, the language barrier, and the lack of employment are some of the many factors that place refugees and other migrants in COVID-19 risk groups ( Ministerio de Salud Pública May 19, 2021 ). With a lack of documents and a closure of public offices, people with irregular migration status are unable to obtain emergency aid the federal government created during the pandemic ( Standley et al, Oct. 2020 ). Brazil's vaccination plan emphasizes “refugiados residentes em abrigos” (refugees in shelters) as a population with increased social and economic vulnerability to COVID-19; nonetheless, migrants are not explicitly included as a priority group within Brazil's national vaccination plans ( Ministerio de Salud Pública Jun.…”
Section: Resultsmentioning
confidence: 99%
“…Almost 80% of Venezuelans have migrated to neighboring countries, with the more than four million Venezuelans residing in Argentina, Brazil, Chile, Colombia, Ecuador, and Peru driving most of the migration in the region ( 4 ). Far from a migration success story, displaced Venezuelans have documented experiences of stigmatization, xenophobia, and violence ( Standley et al, Oct. 2020 ). The unprecedented influx of displaced Venezuelans into neighboring countries has further strained health care and public services in a region devastated by austerity politics and chronically underfunded public healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other indicators of vulnerability have also surged: more than 4 million residents from Venezuela have migrated to neighbouring countries since 2014. 3 Furthermore, the number of persons experiencing homelessness has doubled from 2012 to 2019 in Brazil. 4 Finally, incarcerated prison populations have increased by 206% across Central and South America between 2000 and 2018.…”
mentioning
confidence: 99%